Mixed vector equilibrium problem involving multi-valued mapping - Rahaman, Mijanur; Kilicman, Adem; Ahmad, Rais (Natural Sciences Publishing Corporation, 2016)
In this paper, we consider and study a mixed vector equilibrium problem involving multi-valued mapping in a Hausdorff topological vector space. We prove some existence results for mixed vector equilibrium problem involving multi-valued mapping using KKM theorem, the concept of coercing family for multi-valued mappings and core of a set. The problem of this paper is a combination of a vector equilibrium problem and a vector variational inequality problem and is more general than many existing problems available in the literature.